Synthesis and characterization of grape seeds biochar and iron nanoparticles-added biochar for removal of cadmium from aqueous solutions - Mohammed, El Erchelee Alaa Jassem (2021)
Due to the degradation of environmental quality, particularly in relation to the rising heavy metal concentrations in the environment, methods for removing these contaminants have been widely studied this study aims to investigate the adsorption method for cadmium removal in an aqueous solution using biomass-derived adsorbents. Grape seeds (GS) were used as biomass precursors to prepare grape seeds biochar (GSB) and to synthesize grape seeds-iron nanoparticles (GS-IONPs) for the purpose of removing cadmium ion (Cd) from aqueous solutions using batch adsorption technique. The GSB was prepared at a percentage yield of 48-50% by carbonization of dry grape seeds particles (0.5 mm) at 400 oC under inert gas (N2). The grape seeds iron oxide nanoparticles were prepared by bio-reduction of ferrous chloride salt, using grape seeds water extract. The opt optimum operating conditions of biosynthesis nanoparticles consist of mixing ferric chloride with grape seed water extract in a 2:1 v/v ratio and solution mixture with pH of 3.8. The feasibility of adsorbents to remove Cd from aqueous solutions was investigated through batch studies using the GSB and GS-IONPs, in addition to the commercial charcoal (CC) as adsorbents. Batch experiments were carried out to study the effects of cadmium initial concentrations in the range of 10-25 mg/l, contact time and solution pH (2-12) at solution temperature (30 oC). Batch adsorption of Cd onto the three adsorbents was fitted to the Langmuir, Freundlich, and Temkin isotherm models. It was found that the adsorption of cadmium onto GSB, GS-IONPs and CC followed the Langmuir isotherm model according to the R2 values (0.999 ≥ R2 ≥ 0.970), in addition to the 1/n values, which are less than one. The maximum adsorption capacities were found to be 10.63, 16.3 and 11.12 mg/g onto GSB, GS-IONPs and CC, respectively. Please add a conclusion here.